Geotecnologias aplicadas no diagnóstico e avaliação do saneamento ambiental na região de Porto Murtinho - MS - NELISON FERREIRA CORREA (2024)
The use of technologies such as remote sensing and the Geographic Information System (GIS) for sanitation have been the subject of study, in which these tools provide mapping quickly and economically, also allowing prospective analyzes of past, present and future scenarios. related to the use and conservation of natural resources. Therefore, this thesis used geoprocessing tools to improve decision-making within the scope of environmental sanitation in Porto Murtinho/MS. Porto Murtinho is a municipality located southwest of the State of Mato Grosso do Sul, on the banks of the Paraguay River, in the lower Pantanal complex, covering part of the Chaco Paraguaio and where the Rota Bioceânica will also be located, a bridge that will connect the Brazilian side to the city of Carmelo Peralta, in Paraguay. In this context, the general objective is to evaluate the use of geoprocessing tools to aid decision-making in matters related to sanitation in the Porto Murtinho/MS region, using free and freely distributed tools, in order to develop thematic maps addressing the implementation of a sewage treatment plant and a sanitary landfill. To achieve this purpose, the specific objectives outlined are: conducting a scientometric and bibliometric analysis of the study of geotechnology and sanitation in Porto Murtinho/MS, mapping scientific production and identifying research gaps; discuss the concept and use of geotechnologies in the context of sanitation, offering strategic recommendations for local growth; explore the technical, environmental and legal processes in producing a thematic map for a Sewage Treatment Plant (ETE); and investigate the elements and steps involved in preparing a thematic map for a landfill in Porto Murtinho/MS, considering relevant technical, socio-environmental and legal criteria. Throughout the work, a lack of studies on sanitation in the Porto Murtinho/MS region was observed, mainly with the use of geotechnologies, in addition to the use of free spatial data and free software providing significant and environmentally strategic results, such as the Map of potential areas for installing an E.T.E. and for the implementation of a Sanitary Landfill in the region. The work contributes not only to an in-depth understanding of the interaction between geotechnologies and sanitation in Porto Murtinho/MS, but also to guide future research and development initiatives in the area. These contributions aim to boost the sustainable growth of this location.